Achievement Motivation, Academic Stress and Academic Flow: A Correlation Study on Santri - Jamilah, Zainab Naila Husna; Raharjo, Trubus (ANFUSINA: Journal of Psychology, 2023)
AbstractThis study aims to determine empirically the relationship between achievement motivation and academic stress with acadeic flow in boarding school student. The population in this study were students at a boarding school, while the sampling technique used is purposive sampling technique with a total of 100 subjects. Data collection tools are achievement motivation scale, academic stress scale and academic flow scale with four alternative answers. The data analysis method used is regression of two predictors. The results of the major hypothesis obtained rx12y coefficient of 0.772 with p 0.000 (p < 0.001) which means that there is a very significant relationship between achievement motivation and academic stress with academic flow with an effective contribution of 59,5% so that the major hypothesis is accepted. The results of the first minor hypothesis are accepted because the coefficient between rx1y is 0.638 with a significance level of p of 0.000 (p <0.01) meaning that there is a very significant positive relationship between achievement motivation and academic flow with an effective contribution of 40,7%. The second minor hypothesis  is also accepted because it shows the magnitude of the coefficient between rx2y of -0.705 with a significance of p of 0.000 (p <0.01) so that there is a very significant negative relationship between academic stress and academic flow and has an effective contribution of 49,7%. Based on the results of the study, it shows that achievement motivation and academic stress affect academic flow in students and become a reference for schools to improve students' academic abilities in learning.Keywords: Achievement Motivation, Academic Stress, Academic Flow.